Analisis Pengeluaran Sektor Pariwisata terhadap Ketimpangan Upah Tenaga Kerja di Indonesia - Prasetya, Lalu Muhammad Azmi; Pudjihardjo, M.; Badriyah, Nurul (Jurnal Ekonomi dan Pembangunan Indonesia, 2018)
This study analyses the effect of foreign tourist expenditure, government expenditure and foreign investment on wage inequality between skilled, semi-skilled and unskilled labour in the Indonesian tourism sector. The study uses time series data with a period of 22 years. The method used is Error Correction Model (ECM). The results of this study indicate that foreign tourist expenditure and government expenditure increase inequality in the short term, but in the long run can reduce wage inequality. Meanwhile, foreign investment increases inequality both in the short and long term.